Exploration of the Diversity of Clustered Regularly Interspaced Short Palindromic Repeats-Cas Systems in Clostridium novyi sensu lato - Le Gratiet, Thibault; Le Marechal, Caroline; Devaere, Marie; Chemaly, Marianne; Woudstra, Cédric (Frontiers in Microbiology, 2021)
Classified as the genospecies Clostridium novyi sensu lato and distributed into four lineages (I to IV), Clostridium botulinum (group III), C. novyi and Clostridium haemolyticum are clostridial pathogens that cause animal diseases. C. novyi sensu lato contains a large mobilome consisting of plasmids and circular bacteriophages. Here, we explored clustered regularly interspaced short palindromic repeats (CRISPR) arrays and their associated proteins (Cas) to shed light on plasmid and phage composition and mobility in a study of 58 C. novyi sensu lato genomes. In 55 of these genomes, type I-B (complete or partial), I-D, II-C, III-B, III-D or V-U CRISPR-Cas systems were detected in chromosomes as well as in mobile genetic elements. Type I-B predominated (67.2%) and was the only CRISPR type detected in the Ia, III and IV genomic lineages. Putative type V-U CRISPR Cas14a genes were detected in two different cases: next to partial type-IB CRISPR loci on the phage encoding the botulinum neurotoxin in lineage Ia and in 12 lineage II genomes, as part of a putative integrative element related to a phage-inducible chromosomal island (PICI). In the putative PICI, Cas14a was associated with CRISPR arrays and restriction-modification systems as part of an accessory locus. This is the first time a PICI containing such locus has been detected in C. botulinum. Mobilome composition and dynamics were also investigated based on the contents of the CRISPR arrays and the study of spacers. A large proportion of identified protospacers (20.2%) originated from C. novyi sensu lato (p1_Cst, p4_BKT015925, p6_Cst, CWou-2020a, p1_BKT015925 and p2_BKT015925), confirming active exchanges within this genospecies and the key importance of specific mobile genetic elements in C. novyi sensu lato.